Exercise Prescriptions to Prevent Musculoskeletal Disorders in Dentists - Kumar, Dodda Kiran (JCDR Research and Publications (P) Limited, 2014)
Since the number of dental patients is increasing day by day dentists are forced to spend longer times in dental chairs. This is increasing the prevalence of musculoskeletal disorders in dentists. This article reviews the mechanisms causing musculoskeletal disorders among dentists and also covers the exercises that can be done to prevent them. Exercises that increase the fitness of a dentist are divided into aerobic exercises – concentrating on total body fitness, stretching exercises – that concentrate on the muscles that tend to tighten in prolonged dental postures and strengthening exercises – that concentrate on the muscles that are opposite to the tight muscles. These exercises are made simple and of minimal intensity so that a dentist can practice them independently.